2011
DOI: 10.1175/jas-d-11-046.1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Circulation Regimes and Preferred Regime Transitions in the North Atlantic

Abstract: The persistent regime behavior of the eddy-driven jet stream over the North Atlantic is investigated. The North Atlantic jet stream variability is characterized by the latitude of the maximum lower tropospheric wind speed of the 40-yr ECMWF Re-Analysis (ERA-40) data for the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 67 publications
(124 reference statements)
13
93
0
Order By: Relevance
“…The key result of this letter is that the predictability of the jet decreases systematically, when its trajectory passes through this region. Franzke et al [2012] and Hannachi et al [2012] suggest that when the jet is shifted to the north, it tends to transition south via wave breaking. This transition implies temporary disruption of the zonal flow and passage of trajectories through the less predictable region of PCspace associated with weak or split jets.…”
Section: Flow-dependent Predictability Of the Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…The key result of this letter is that the predictability of the jet decreases systematically, when its trajectory passes through this region. Franzke et al [2012] and Hannachi et al [2012] suggest that when the jet is shifted to the north, it tends to transition south via wave breaking. This transition implies temporary disruption of the zonal flow and passage of trajectories through the less predictable region of PCspace associated with weak or split jets.…”
Section: Flow-dependent Predictability Of the Jetmentioning
confidence: 99%
“…[4] Recent results [Woollings et al, 2010;Franzke et al, 2012;Hannachi et al, 2012] suggest that statistics of North Atlantic eddy-driven jet indices possess significant inhomogeneities, indicating the presence of three regimes: a regime with the maximum wind-speed of the jet shifted south of its climatological mean latitude, one with it close to the mean latitude and one with it shifted north of the mean latitude. Further evidence has been found that the skill in forecasting the jet appears to vary with these regimes, with the skill being lowest when the forecast starts with the jet in the north regime [Frame et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with the large-scale flow effect on local flow adjustment of Roebber (2009), where it is found that the forcing effect of cyclogenesis on blocking is controlled by the state of the planetary flow. Franzke et al (2011) applied a hidden Markov model (HMM) to the jet time series and identified C → N → S → C as the main transition loop. The difference between their results and ours is due to the difference in data and methodologies used in both analyses.…”
Section: Transition Probabilities Between Jet Stream Positionsmentioning
confidence: 99%
“…As shown in several studies and mentioned above, in particular the synoptic-scale Rossby wave breaking drives not only most atmospheric teleconnection patterns (Feldstein, 2003;Benedict et al, 2004;Franzke et al, 2004;Riviere and Orlanski, 2007;Woollings et al, 2008;Franzke et al, 2011a) but also transitions between atmospheric flow regimes (Benedict et al, 2004;Franzke et al, 2004;Woollings et al, 2008;Riviere, 2010;Riviere et al, 2010;Franzke et al, 2011b).…”
Section: Discussionmentioning
confidence: 68%
“…Recent work elaborated the role of synoptic-scale Rossby wave breaking for such transitions (e.g. Benedict et al, 2004;Franzke et al, 2004;Woollings et al, 2008;Riviere, 2010;Riviere et al, 2010;Franzke et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%